Menumbuhkan Minat Membaca dan Menghafal Ayat-Ayat Al-Kitab Melalui Model Pembelajaran Terpadu - Hotland Napitupulu (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This study aims to foster interest in reading and memorizing Al-Kitab Verses in the material I am the Image of Allah in Christian Religious Education subjects through an Integrated learning model. This research was conducted by fostering interest in reading and memorizing verses of the Bible for grade IX students of SMPN 3 Kisaran, Asahan district for the 2019/2020 school year. The results of the learning process before the study reached an average value of 68%. After being motivated, the research was carried out through the first cycle and the second cycle of reflection and the recommendation of the average value reached 85%, meaning there was an increase of 17%. Learning outcomes in the first cycle reached an average value of 80% after the first cycle and second cycle, reflection and recommendation of the average value reached 85%. Keywords: reading; memorize; integrated learning Abstrak: Penelitian ini bertujuan untuk menumbuhkan minat membaca dan menghafal Ayat-Ayat Al-Kitab pada materi Aku Adalah Citra Allah mata pelajaran Pendidikan Agama Kristen melalui model pembelajaran Terpadu. Penelitian ini dilakukan dengan menumbuhkan minat membaca dan menghafal ayat-ayat al-kitab siswa kelas IX SMPN 3 Kisaran kabupaten Asahan tahun ajaran 2019/2020. Hasil proses belajar sebelum penelitian mencapai nilai rata-rata 68%. Setelah termotivasi dilakukan penelitian melalui siklus I dan siklus II refleksi dan rekomendasi nilai rata-rata mencapai 85 % berarti ada peningkatan sebesar 17%. Hasil belajar pada siklus I mencapai nilai rata-rata 80% setelah siklus I dan siklus II, refleksi dan rekomendasi nilai rata-rata mencapai 85%. Kata Kunci: membaca; menghafal; pembelajaran terpadu